PENGUATAN KOMPETENSI LITERASI KEUANGAN DIGITAL GURU DI KECAMATAN JABUNG KABUPATEN MALANG - Perdana, Sukma; Kristiawan, Indria; Efendiy, Khoirul; Umamy, Etty (ABIDUMASY, 2025)
Strengthening digital financial literacy is an urgent need in the 21st-century education ecosystem, as teachers play a strategic role both as facilitators of learning and as managers of school financial administration. This community service program aimed to enhance teachers’ knowledge, skills, and self-efficacy in utilizing simple digital technology based on Google Sheets for cash recording, budgeting, and financial reporting. The partner of this program was SDN 1 Kemantren, Jabung, Malang Regency, with active participation from teachers as participants. The implementation methods included socialization, workshops, practicum, and mentoring, which were systematically arranged to provide hands-on experience, repeated practice, and structured feedback. The results indicated a significant improvement in teachers’ conceptual understanding, their ability to prepare monthly financial reports, and their collaborative skills in developing digital recording templates. These findings demonstrate that digital financial literacy not only strengthens technical competencies but also contributes to the development of 21st-century skills (critical thinking, creativity, collaboration, communication). The implication is that digital financial literacy should be systematically integrated into school curricula and teacher professional development programs, so that these best practices can be expanded to other schools and foster a financial literacy culture that is adaptive to technological advancements in education.